PROSPEK KEBERLANJUTAN PROGRAM KAWASAN RUMAH PANGAN LESTARI - Saptana, nFN; Indraningsih, Kurnia Suci; Ashari, nFN; Mardiharini, Maesti (Analisis Kebijakan Pertanian, 2021)
The use of backyard land (pekarangan) by community has not been optimal yet. As a component of food diversification effort, Ministry of Agriculture has developed a program called Sustainable Food-Reserved Garden (SRFG) that empowers Women Farmer Group (WFG) to be able to provide a diverse and nutritious food for their families continuously. The purpose of this study was to evaluate SFRG activities that include an assessment of policy concepts, implementation, output, and outcomes. Coverage of this study was at national level with indepth analysis was conducted in two selected provinces, namely East Java and West Kalimantan. Data collection in these two provinces used survey and interview to 39 WFGs. Data was analysed using descriptive and a statistical methos using Partial Least Square (PLS). Results of this study showed that the SFRG program performances in the two provinces were mostly moderate to good. However, if there were no supporting policies and programs, the SFRG program was predicted will not be sustainable. Several factors affecting the sustainability of SFRG were (i) availability of planting media; (ii) availability of water sources and their efficient use; (iii) market institutions (mini markets, village markets) and business partnerships with collectors and supermarket; and (iv) processing of results that can increase value-added and SFRG networks. The policy implications for the sustainability of SFRG program are determined by the implementation aspects, supporting aspects, promotion aspects, and the synergy between programs across sectors. AbstrakPemanfaatan lahan pekarangan yang dilakukan masyarakat dinilai belum optimal. Sebagai komponen dari upaya diversifikasi pangan, Kementerian Pertanian mengembangkan program Kawasan Rumah Pangan Lestari (KRPL) yang merupakan kegiatan Kelompok Wanita Tani (KWT) di lahan pekarangan untuk menghasilkan aneka pangan bergizi untuk keluarganya secara berkelanjutan. Tujuan penelitian ini adalah melakukan evaluasi program KRPL yang mencakup aspek konsep kebijakan, implementasi, output dan outcome. Cakupan penelitian bersifat nasional, dengan pendalaman dilakukan di dua provinsi terpilih, yaitu Jawa Timur dan Kalimantan Barat. Pengumpulan data di kedua provinsi tersebut dilakukan dengan metoda dan wawancara terhadap 39 KWT. Analisis dilakukan secara diskriptif kualitatif dan analisis statistik dengan menggunakan Partial Least Square (PLS). Implementasi program KRPL menunjukkan kinerja sedang hingga baik. Meskipun demikian, jika tidak ada kebijakan dan program pendukung maka program KRPL terancam tidak berkelanjutan. Faktor-faktor yang paling berpengaruh terhadap keberhasilan program KRPL adalah (a) ketersediaan media tanam; (b) ketersediaan sumber air dan pemanfaatannya secara efisien; (c) adanya kelembagaan pasar (kios desa, pasar mini, pasar desa) dan kemitraan usaha (pedagang pengumpul, pedagang keliling); dan (d) pengolahan hasil yang dapat meningkatkan nilai tambah dan jejaring KRPL. Implikasi kebijakan untuk keberlanjutan program KRPL sangat ditentukan oleh aspek pelaksanaan, aspek pendukung, dan aspek promosi, serta sinergi antar program lintas sektor.
Keywords: evaluasi program; keberlanjutan usaha pekarangan; rumah pangan lestari; food reserve garden; program evaluation; sustainable backyard farming